Ana M. López : Essays. - López, Ana M.; Podalsky, Laura; Tierney, Dolores (Albany : State University of New York Press, 2023)
Brings together Ana M. López's field-defining essays on Latin American film and media in one indispensable volume.
Memories of Underdevelopment: History as the Present -- The Jackal of Nahueltoro: A Criminal Wild Child -- One Way or Another: Another Marginalism -- At the Boundaries of Fiction and Documentary: Historical Reconstruction and the Ukamau Group -- Conclusion -- 18 A Poetics of the Trace (2014) -- Santiago: Othering the Self and Exposing the Process -- Jogo de Cena: A Manual for Emotion -- Alamar: To the Sea -- Conclusion -- Part 3. Intersections: Race, Ethnicity, and Gender -- Editors' Introduction -- 19 Not Only a Question of Color: Afro-Latino/a Images in Latin American Cinema Today (1992) -- 20 African Roots: Images of Black People in Cuban Cinema (1988) -- 21 Sergio Giral on Filmmaking in Cuba (1986-1987) -- 22 Are All Latins from Manhattan? Hollywood, Ethnography, and Cultural Colonialism (1991) -- The Good Neighbor Policy: Hollywood Zeroes In On Latin America -- The Transition: From Indifference to "Difference" across the Bodies of Women -- The Perfect "Good Neighbor": Fetishism, Self, and Others -- "Are All Latins from Manhattan?" -- 23 Greater Cuba (1996) -- The First Generation -- The Second Generation -- The Third Generation -- Postscript: The Special Period -- 24 I (Also) Love Ricky: The Oft-Forgotten Cuban-in-the-Text (2012) -- Part 4. Final Thoughts, Metacritical Reflections -- 25 López on López: Liminal Words (2012) -- "Siete Veces Ana": An Afterword -- Notes -- Works Cited -- Index.
Description based on publisher supplied metadata and other sources.
JSTOR
Keywords: Motion pictures -- Latin America -- History; Motion pictures -- Social aspects -- Latin America; Mass media -- Latin America -- History; Mass media -- Social aspects -- Latin America; Latin Americans in motion pictures; Cinéma -- Amérique latine -- Histoire; Cinéma -- Aspect social -- Amérique latine; Médias -- Amérique latine -- Histoire; Médias -- Aspect social -- Amérique latine; Latino-Américains au cinéma.; History & Criticism; Latin America; HISTORY; Radio; PERFORMING ARTS; Television; Film & Video; Latin Americans in motion pictures; Mass media; Mass media -- Social aspects; Motion pictures; Motion pictures -- Social aspects; Latin America; Electronic books; History